MAKNA KATA-KATA MUTIARA (QUOTES) BJ HABIBIE : TINJAUAN KESANTUNAN BERBAHASA - Wijaya, Prasetya W E; Tulung, Golda J.; Pandean, Mariam (Kajian Linguistik, 2019)
Abstrak.This study aims to describe the meaning of BJ Habibie's Quotes based on linguistic politeness. Data sources were  collected  from  BJ Habibie Quotes  through online news. The research method that used in this research is descriptive qualitative method. Quotes of BJ Habibie in this study has a strong principle of linguistic politeness which includes; (1) formality scale, (2) hesitancy scale, and (3) equality scale, and as interpreted as affective meaning. The result of this study was obtained to a strong principle in every quotes that have a common understanding to the linguistic politeness principle that has been expressed by Robin Lakoff.Keywords : linguistic politeness, quotes, Bj Habibie